(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Three yearling uncastrated males of Sudan Nubian goatsranging in weight between 14 and 20 kg were used in a 3x3 latin squaredesign experiment with the objective of studying the effects of feed andwater restriction on dry matter intake (DMI), water intake, digestibility ofnutrients, rumen components, blood urea-N (BUN), rectal temperatureand respiration rate. The experiment consisted of three treatments:Adlibitum feed and water, feed restricted to 50% of adlibitum level withadlibitum water, water restricted to 50% of adlibitum level with adlibitumfeed. The results revealed no significant treatment effects on water intake,urine volume, rectal temperature and respiration rate. However, DMIdiffered significantly between treatments. The adlibitum provision ofwater resulted in insignificant higher water intake compared with theother two treatments. Rectal temperature was higher in water restrictedgoats than in feed restricted goats, whereas respiration rate decreasedinsignificantly with both feed and water restrictions. Feed and waterrestrictions had no effect on the digestibility coefficients of the variousnutrients. Water restricted goats showed, however, different trends exceptfor ether extract digestibility which tended to decrease. Treatment had nosignificant effect on the total digestible nutrients (TDN) values. The TDNtended to be higher with water restriction. There was no significanttreatment effect on rumen pH, ammonia-N (NH3 -N) and BUN. Feed andwater shortage did not significantly affect digestibility of the proximatecomponents but tended to slightly affect rumen metabolites, BUN,respiration rate and rectal temperature.